Inuit and whaling schooner crew members in covered whaleboat, Hudson Bay, Canadian Arctic (Ownership Statement: Mystic Seaport, 1897)
Several Inuit and whaling schooner crew members are sitting inside a covered whaleboat in Hudson Bay, ca. 1897-1912. Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as Photo #191. During the period of floe whaling in May and June, the whaleboats were hauled across the ice to open water and used to hunt whales. Each boat was also fitted with a framework and canvas cover so it could be used for shelter. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.